1975
DOI: 10.1093/ajcn/28.7.681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lactose and lactase preparation on the intestinal absorption of calcium and magnesium in normal infants

Abstract: Effects of dietary lactose and a lactase preparation on the intestinal absorption of calcium and magnesium were studied in 3 groups under 8 months of age; infants on a proprietary milk, infants on a lactose-free milk, and infants on a proprietary milk to which a lactase preparation was added. The intestinal absorption of both elements was reduced in infants on a lactose-free milk and enhanced in infants who were fed on a proprietary milk and given a lactase preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 9 publications
4
25
0
2
Order By: Relevance
“…However, in the latter study, lactose and calcium were ingested as a bolus containing very high quantities (500 mg of Ca, 100 g of lactose). The present study is closer to those of Debongnie et al (1979) and Kobayashi et al (1975), both of which showed that hydrolysed lactose resulted in an increase in calcium absorption. However, the first one reported that hydrolysed lactose had a similar positive action in both control and lactase-deficient subjects, while we observed this effect only in the lactase-deficient ones.…”
supporting
confidence: 90%
“…However, in the latter study, lactose and calcium were ingested as a bolus containing very high quantities (500 mg of Ca, 100 g of lactose). The present study is closer to those of Debongnie et al (1979) and Kobayashi et al (1975), both of which showed that hydrolysed lactose resulted in an increase in calcium absorption. However, the first one reported that hydrolysed lactose had a similar positive action in both control and lactase-deficient subjects, while we observed this effect only in the lactase-deficient ones.…”
supporting
confidence: 90%
“…Similar to the data from rodents, calcium absorption in neonates is enhanced by the lactose content of milk (317,318). Intestinal absorption and retention of calcium increase with both postnatal age and gestational age, with additional variations superimposed by the composition of the milk (45,221,256,485,604,613).…”
Section: Human Datasupporting
confidence: 69%
“…Por exemplo, em estudo sobre o balanço de Ca em crianças de 8 meses de idade, utilizando-se três fórmulas infantis (uma padrão, uma livre de lactose e uma fórmula tratada com lactase), observou-se que a absorção do elemento foi de 60% para a fórmula padrão, de 36% para a lactose-livre, e de 72% para lactase tratada (31). Estes resultados, aparentemente contraditórios, sugerem que a glicose e a galactose liberada da hidrólise da lactose são igualmente eficientes na absorção do Ca alimentar (24,27).…”
Section: Lactoseunclassified